211k views
3 votes
Select the equivalent expression.

(a^5 * 2^3)^3 = ?


1. a^8*2^9

2. a^15*2^6

3. a^8*2^6

3. a^15*2^9

User Giohji
by
3.8k points

2 Answers

5 votes

Answer:

a^15 * 2^9

Explanation:

(a^5 * 2^3)^3 =

= (a^5)^3 * (2^3)^3

= a^(5 * 3) * 2^(3 * 3)

= a^15 * 2^9

Answer: the second choice 3.

User Jwag
by
5.5k points
3 votes

Answer:

3. a^15*2^9

Explanation:

We know that (a * b) ^c = a^c * b^c

(a^5 * 2^3)^3

a^5^3 * 2^3^3

And we know that a^b^c = a^(b*c)

a^(5*3) * 2^(3*3)

a^15 * 2^9

User Kroegerama
by
5.3k points